Rudy [videorecording (DVD)] - Anspaugh, David; Astin, Sean; Beatty, Ned; Dutton, Charles S. (Columbia TriStar Home Video, 2000)
Although people have told Rudy all his life he's not good enough, smart enough or big enough, nothing can stop his impossible dream of playing football for Notre Dame.